Training and academic demands are associated with sleep quality in high-performance "dual career" student swimmers. - Astridge, D.; Sommerville, A.; Verheul. M.; Turner. A. P. (European Journal of Sport Science, 2020)
Dual career collegiate athletes, who combine sporting endeavours with academic studies, are commonplace in high-performance sport. Sleep is an important aspect of physical and psychological recovery for athletes, plays a role in memory and learning and is associated with academic achievement. The aim of this study was to assess variations in sleep characteristics of collegiate swimmers to understand the incidence of poor sleep, and which stressors might contribute towards this. A total of 22 (male n = 13, female n = 9) high-performance student swimmers (mean ± SD; age 20 ± 2 years) participated in this study. Sleep/wake behaviour was assessed using the Pittsburgh Sleep Quality Index each month over a twelve-month period. Additionally, academic and sporting commitments were quantified on a monthly basis and summarised as 4 stressors: average weekly training hours, total number of competitive races, total number of academic assessments, and average weekly learning hours. On average across the 12-month period, 41.7% of athletes reported poor sleep. The latest bedtimes, wake times and longest sleep durations were found in the months where academic and training demands were lowest. A statistically significant positive association was identified between median sleep quality scores and mean number of academic assessments (Rho(12) = 0.71, p=0.005). Hierarchal linear modelling analysis determined that number of academic assessments best predicted sleep quality within this cohort. The present study highlights the need for those working with athletes who have competing academic demands to consider sleep quality, and its potential impact on performance and wellbeing.